Perancangan UI/UX Sistem Informasi Laporan Pernikahan Berbasis Web pada Disdukcapil Kota Palembang - Syahadatilah Syahadatilah; Achmad Husein Darmawan; Edi Surya Negara (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to design the UI/UX of a web-based marriage report information system at the Department of Population and Civil Registration of Palembang City. The system, named SILAPNIK, was developed using the Waterfall method to address the challenges of manual data management. This research employs a qualitative approach with observation, interviews, and documentation techniques. The design was created using Figma, resulting in nine interconnected pages: login, dashboard, report data, add/edit report, report detail, verification, print report, archive, and user profile. The results show that the UI/UX design facilitates structured data entry, search, validation, verification, and reporting of marriage data. Key features include search and filter functions, color-coded status badges, NIK validation, document upload, confirmation modals, and real-time notifications. The prototype demonstrates that a simple, consistent, and user-friendly interface can improve administrative efficiency. The study concludes that SILAPNIK's UI/UX design serves as a viable foundation for developing an operational system to support civil registration services. However, further development is needed to integrate databases, access rights, and digital archiving systems.